2008
DOI: 10.1515/revce.2008.24.4-5.159
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation of Partially Miscible Solvent Systems: Flow Phenomena and Heat and Mass Transfer Applications

Abstract: The phenomena associated with phase separation via spinodal decomposition (SD) and nucleation of binary and ternary partially miscible solvent systems are reviewed. The pertinent literature includes many theoretical, numerical and experimental studies which were conducted in order to follow the flow phenomena during the phase separation of solutions of critical and off-critical compositions. The unique characteristics of phase transition in partially miscible solvent systems include efficient mass transfer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 107 publications
1
10
0
Order By: Relevance
“…(21) represent the heating rate and the depth (in terms of temperature) of the penetration into the unstable region of the coexistence curve. This agrees with previous findings that increasing these two parameters results in a higher growth rate and movement of the separating domains/droplets during the phase transition (Ullmann et al, 2008). It is of interest to examine whether the heat transfer augmentation factor AF can be attributed to the lateral velocity v of the separating droplet/domain.…”
Section: Experiments With Lcst Systemssupporting
confidence: 91%
See 2 more Smart Citations
“…(21) represent the heating rate and the depth (in terms of temperature) of the penetration into the unstable region of the coexistence curve. This agrees with previous findings that increasing these two parameters results in a higher growth rate and movement of the separating domains/droplets during the phase transition (Ullmann et al, 2008). It is of interest to examine whether the heat transfer augmentation factor AF can be attributed to the lateral velocity v of the separating droplet/domain.…”
Section: Experiments With Lcst Systemssupporting
confidence: 91%
“…The scaling exponents are confirmed by theoretical studies [see Bray (1994) for a review] based on modeling the phase transition with one of the variations of the van der Waals square gradient model, known as Cahn-Hilliard theory, model H, the diffuse interface (DI) model, or Ginzburg-Landau phase-field theory. Reviews on spinodal decomposition can be found in the literature (e.g., Gunton et al, 1983;Ullmann et al, 2008).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the previous research [29] proved that the droplet coalescence was governed by convection. It should be noted that the evolution of the separated domains during the spinodal decomposition is difficult to analyze quantitatively, owing to the unsharp interfaces.…”
Section: In-situ Observation Of Liquid-liquid Phase Separation Behaviorsmentioning
confidence: 97%
“…Furthermore, the impurities in solutions present no noticeable effect on the phase separation. Therefore, the LCST solutions (such as triethylamine/water, 2-butoxyethanol/water, and lutidine/water) present great potential in realizing the multi-goals mentioned above [29]. For instance, Xing et al [30] proved that the Nusselt number increases about 100% when the coolant in microchannels changes from water to an aqueous triethylamine solution.…”
Section: Introductionmentioning
confidence: 99%